Histocompatibility antigens in inflammatory bowel disease. Their clinical significance and their association with arthropathy with special reference to HLA-B27 (W27). Issue 11 (November 1976) - Mallas, E G; Mackintosh, P; Asquith, P; Cooke, W T
Abstract : Histocompatibility (HLA) antigen phenotypes have been studied in 100 patients with ulcerative colitis, 100 with Crohn's disease, and 283 normal controls. In addition the incidence of ankylosing spondylitis, sacroiliitis, and "enteropathic" peripheral arthropathy was determined in the patients with inflammatory bowel disease (IBD). There was no significant difference in antigen frequency between patients and controls. However, the incidence of HLA-B27 was increased in the patients complicated by ankylosing spondylitis and/or sacroiliitis in both ulcerative colitis and Crohn's disease. In contrast, none of the 29 IBD patients with "enteropathic" peripheral arthropathy had B27 antigen. Furthermore, ankylosing spondylitis was found more frequently in ulcerative colitis bearing HLA-B27 compared with non-B27 patients (P less than 0-01). The same was found in Crohn's disease, although this difference was not statistically significant. In addition, 12 of 14 ulcerative colitis patients and five out of six Crohn's patients with HLA-B27 had total colitis, compared with the frequency of total colitis in non-B27 patients (P less than 0-024 and less than 0-03 respectively). The data suggest that B27 histocompatibility antigen could be a pathogenetic discriminator between the arthropathies in IBD and may be of prognostic significance with respect to extension and severity of the disease.